Infrastructure, and Labor Market on Poverty in Indonesia - Adlina Khairunnisa; Prayudha Ananta (Riset Akuntansi dan Bisnis Indonesia, 2026)
Purpose: This study examines the influence of institutional, quality, infrastructure development, and labor market conditions on poverty reduction in Indonesia. Methodology: This study employs a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM). This study utilizes secondary data obtained from the National Research and Innovation Agency (BRIN), Statistics Indonesia (BPS), the Worldwide Governance Indicators (WGI), and several other official institutions. The variables examined in this study include institutions, infrastructure, the labor market, and poverty. Results: The findings reveal that institutional quality, infrastructure, and labor market conditions exert negative and statistically significant effects on poverty. Among the independent variables, the labor market made the strongest contribution to poverty reduction. Conclusions: Improvements in institutional quality, infrastructure provision, and labor market performance are crucial for reducing poverty in Indonesia. The labor market is identified as the most influential factor because it directly affects employment opportunities and household incomes. Limitations: This study is limited to three explanatory variables, while other factors beyond the research model may also contribute to the poverty dynamics. Contribution: This study provides empirical evidence of the importance of institutional strengthening, infrastructure expansion, and labor market development as strategic instruments for poverty alleviation in Indonesia.